Experimental and validation of significance and accuracy of oxidized low-density lipoproteins and myeloperoxidase in the screening of cardio-vascular disease - Mandsorwale, Deepti; Sharma, Bindu (ScienceRise: Medical Science, 2022)
The aim. To access the superiority of myeloperoxidase & oxidized low-density lipoproteins over each other acts as a better predictive marker gaining information regarding the severity of cardiovascular disease. Materials and methods. 215 subjects are taken into consideration of which 54 are healthy controls, 52 are from stable angina pectoris, 53 are taken from unstable angina pectoris and 56 subjects are from acute myocardial infarction. Lipid profile parameters, oxidative stress markers, plasma myeloperoxidase and plasma oxidized low density lipoproteins were estimated by kit methods, thiobarbituric acid reactive substances method, and colorimetric assay, sandwich and competitive enzyme linked immunosorbent assay techniques, respectively. Results were present as mean ± SD, p-values <0.05 as significant, and Student’s unpaired “t” test. Comparative analysis by box and whiskers plot to check skewness and deviations within the values. Data analysis was performed by software package SPSS version 17.0. Results. The oxidized low density lipoproteins levels found significantly elevated in all three cases subgroup contrary to insignificant levels of myeloperoxidase in stable angina pectoris compared to control. Box and whisker plot of myeloperoxidase levels showed no skewness in stable angina pectoris (non-significant), whereas unstable angina pectoris and acute myocardial infarction showed right skewness (highly significant), whereas plots of oxidized low-density lipoproteins show extensive interquartile range in the stable angina pectoris subgroup, suggesting scattered deviation in the mean values compared to unstable angina pectoris and acute myocardial infarction subgroup. Conclusions. The study concluded that significantly elevated level of oxidized low-density lipoproteins in stable angina pectoris, unstable angina pectoris, and acute myocardial infarction subgroups with a scattered deviation of oxidized low density lipoproteins levels in the stable angina pectoris subgroup reflects its low prognostic reliability compared to plasma myeloperoxidase with marginal deviation and in insignificant elevation in stable angina pectoris. Thus, plasma myeloperoxidase and oxidized low density lipoproteins levels serve as independent predictors of cardiovascular disease, but plasma myeloperoxidase levels predict an increased risk over oxidized low density lipoproteins for subsequent cardiovascular events in stable and unstable angina and extend the prognostic information gained from traditional biochemical markers